pharmaceutical-sciences 2019
DOI: 10.36468/pharmaceutical-sciences.554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuing Pharmacy Education on the Knowledge, Attitude and Practice of Community Pharmacists about ADR Monitoring and Reporting

Abstract: Adverse drug reactions (ADRs) are the most common causes of morbidity, mortality and poor economical outcomes. Therefore post marketing surveillance is very important for monitoring the risks and benefits of pharmaceutical products after they have been marketed. The roles of pharmacists have expanded to other aspects of patients' care, which include reporting ADR, improving patients' health and economic outcomes [1] . The pharmacists traditionally have been playing the role of preparing and dispensing medicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…18,19 The awareness was increased among the study participants after the educational intervention and similar results were reported by the studies conducted in neighboring states like Tamil Nadu and Kerala. 6,20 The current study observed around half of the study participants still believe the medicines are safe if the patients takes those at the right dose, right route and at the right time, even during the post interventional stage. This implies the need for hands-on training, continuous evaluation and education and clinical education to all the community pharmacists.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…18,19 The awareness was increased among the study participants after the educational intervention and similar results were reported by the studies conducted in neighboring states like Tamil Nadu and Kerala. 6,20 The current study observed around half of the study participants still believe the medicines are safe if the patients takes those at the right dose, right route and at the right time, even during the post interventional stage. This implies the need for hands-on training, continuous evaluation and education and clinical education to all the community pharmacists.…”
Section: Discussionmentioning
confidence: 67%
“…4 Continuous education programs for healthcare professionals on pharmacovigilance, increased accessibility of yellow cards, pharmacists' ward round participation and active training to health care professionals were proposed by various research studies to improve the knowledge and attitude towards ADR identification and reporting. 3,5,6 Previous studies has revealed that pharmacists can be handy reporting ADRs timely. Preferably in community pharmacy setup because of their comprehensive knowledge of drugs and the closeness to the ADRs effect on patients every day.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, educational material such as handouts and job aids were distributed. Some interventions included practical sessions on completing AE reporting forms, 18 feedback or reminders to HCP, 19 and follow-up contacts to assess changes in AE reporting 20 or to address any challenges encountered. 21 There was an increase in the knowledge, attitude and practice skills of PV and ADR reporting rates for most educational interventions.…”
Section: Educational Interventionsmentioning
confidence: 99%
“…In some cases, educational material such as handouts and job aids were distributed. Some interventions included practical sessions on completing AE reporting forms (18), feedback or reminders to HCP (19), and follow-up contacts to assess changes in AE reporting (20) or to address any challenges encountered (21).…”
Section: Educational Interventionsmentioning
confidence: 99%